Estudios inmunológicos como parte del Control Médico del Entrenamiento en luchadores élite durante ciclo olímpico 2021-24 - Vidal Martinez, T. (Revista Cubana de medicina del deporte y la cultura fisica, 2019)
The immune response in elite athletes during sports training, competitive events, and physiological and psychological metabolic stress undergoes modifications. These variations in the immune response reflect the magnitude of the psychophysiological stress experienced by athletes during the different stages of the sports training cycle. In the Sports Medicine Institute, the evaluation of the immune answer will begin as part of the medical control of the training during the Olympic cycle 2021-2024 in elite athletes of the wrestling sport: female, male and Greco-Roman. The research will describe the behavior of the immune response in the different stages of the Olympic training cycle. The modifications in the immunological variables of the innate, humoral and cellular immune response during the Olympic training cycle, as well as the possible finding of transient states of secondary immunodeficiency`s that will be evaluated by immunochemical techniques, molecular biology and flow cytometry, which will allow the physician of the equipment during the different stages of sports training; to identify the immunological variables that can serve as alarm signals and that reflect the magnitude of psychophysiological stress experienced by athletes during the Olympic training cycle in order to collaborate with a better therapeutic management by medical specialists in sports medicine.